The Effectiveness of E-Comic Learning Media Based on Teaching Factory on Creative Projects and Entrepreneurship in Increasing Learning Outcomes and Interest in Entrepreneurship - Anis Setyaningsih; Norida Canda Sakti; Tri Sudarwanto (Budapest International Research and Critics University, 2022)
This study aims to test the effectiveness of teaching factory-based mobile e-comic learning media on Creative Projects and Entrepreneurship subjects with e-commerce menus in improving student learning outcomes and entrepreneurial interest in Vocational High Schools. The type of research used is experimental research using the Pretest-Posttes Control Group design. The research was conducted at SMK Negeri 12 Surabaya with the research subjects of class XI Metal 1 as the experimental class and class XI Metal 2 as the control class. Using the analysis technique of independent t-test test and N-gain test to measure the effectiveness of learning outcomes, as for measuring the effectiveness of interest in entrepreneurship, it was analyzed using the Mann-Whitney U test and Wilcokson test because the data results were not normal so using non-parametric data analysis. The results of this study are (1) the average pretest value of the experimental class is 64.75 and the posttest value is 80.50 while in the control class the average pretest is 65.50 and the posttest value is 70.00 (2) Independent t-test shows the results where Tcount > T table is 3.438 > 2.024 (0.<0.05) and the significance value is 0.001 <0.05; (3) The N-gain test for experimental class students' learning outcomes is 0.4 and the control class N-gain is 0.1; (4) Mann Whiteny Test with Posttest results for both classes obtained a significance of 0.000 < 0.05; (2) Wilcokson's test with a significance result of 0.000 <0.05 with an average value of 10.50 for the experimental class while in the control class of 8.50.